Akibat Hukum Dari Pemutusan Kontrak Secara Sepihak - Nurainy Usman; Merry Tjoanda; Saartje Sarah Alfons (Faculty of Law, Universitas Pattimura, 2021)
This study aims to determine how the arrangements for the unilateral termination of the contract/agreement and what are the legal consequences arising from the unilateral termination of the contract. The research method used is normative juridical. The approach used in this research is the statute approach and the case approach, and the conceptual approach. The conclusion of the research results is that; contract termination arrangements and legal consequences are regulated in Articles 1266, 1267, 1243 and 1365 of the Civil Code. The conditions for an agreement to be canceled unilaterally are that the agreement must be reciprocal, there is default, and the cancellation must be requested from the judge. Unilateral termination of the agreement due to default without going through the court is an act against the law. The legal consequence of the unilateral termination of the agreement due to default is a claim for compensation from the party who feels aggrieved. The Civil Code does not explicitly regulate the differentiation of compensation as a result of default with compensation as a result of an act against the law. Based on the research results, it is found that compensation as a result of default is compensation in the form of material, while compensation for an illegal act is compensation in the form of material and immaterial. It is hoped that in the future there will be clear regulations regarding compensation as a result of default and compensation as a result of acts against the law.